Test of Randomness of Residuals for the Buchanan-three-phase Model used in the Fitting the Growth of Paracoccus sp. SKG on Acetonitrile - Gunasekaran, Baskaran; Shukor, M.S.; Masdor, N.A.; Shamaan, N.A.; Shukor, M.Y. (Journal of Environmental Bioremediation and Toxicology, 2015)
Organonitriles are classified as priority pollutants. They are carcinogenic and mutagenic. Bioremediation of acetonitrile, an organonitrile, has been touted as a more economical and feasible method compared to physical and chemical approaches. In this work, we model the growth of growth of Paracoccus sp. SKG on acetonitrile from published literature to obtain vital growth constants. We discovered that the Buchanan-three-phase model via nonlinear regression utilizing the least square method was the very best model to explain the growth curve. An important consideration that has not been highlighted enough is that the residuals of the model must be random. In order for randomness to be met, we perform the Wald–Wolfowitz runs test. The results showed that the number of runs was 5, the expected number of runs under the assumption of randomness was 3.857, indicating the series of residuals had adequate runs. The pvalue obtained was greater than 0.05, therefore the null hypothesis is not rejected indicating no convincing evidence of non-randomness of the residuals and they do represent noise.